Linguistic landscapes in multilingual urban settings: Insights from translation perspectives - Napu, Novriyanto (Studies in English Language and Education, 2024)
A multilingual urban area is a translation space that allows the exchange of ideas across languages and cultures. Yet, little research has examined how translation plays a role in shaping linguistic landscapes that depict coexisting languages in public spaces. This paper aims to examine the linguistic landscape of public signage from the viewpoint of translation. A total of 123 bilingual signage was collected from the linguistic landscape of Gorontalo City, an emerging tourism industry with an interesting multilingual setting in Eastern Indonesia. The data were analyzed using the translation category of multilingual writing developed by Reh (2004) and Edelman (2010) to provide an understanding of the translational practice evident in the signage. The analysis also looked at the direction of the translated signage, including official and non-official translation based on the linguistic landscape orientation (top-down and bottom-up), as well as translation to demonstrate collective identity. Translation practices, categorized into word-for-word (67 items), free (8 items), partial (11 items), and non-translation (37 items), demonstrate a growing trend toward linguistic diversity. The top-down approach is evident in official translations (50 items) by government entities, while non-official translations (73 items) dominate commercial spaces. Arabic, displayed alongside Indonesian and English, symbolizes religious identity in public signage. Overall, Gorontalos linguistic landscape reflects a shift to bilingualism, particularly with widespread English translations. Its linguistic landscape showcases a dynamic interplay of language, translation, and cultural identity in an evolving urban environment.